2021
DOI: 10.48550/arxiv.2104.09389
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thermonuclear Explosions and Accretion-induced Collapses of White Dwarfs in Active Galactic Nucleus Accretion Disks

Jin-Ping Zhu,
Yuan-Pei Yang,
Bing Zhang
et al.

Abstract: White dwarfs (WDs) embedded in gaseous disks of active galactic nucleus (AGNs) can rapidly accrete materials from the disks and grow in mass to reach or even exceed the Chandrasekhar limit. Binary WD (BWD) mergers are also believed to occur in AGN accretion disks. We study observational signatures from these events. We suggest that mass-accreting WDs and BWD mergers in AGN disks can lead to thermonuclear explosions that drive an ejecta shock breakout from the disk surface and power a slow-rising, relatively di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…The unique environments in AGN disks are expected to give rise to a wealth of other interesting phenomena, such as the tidal disruption of a star by a neutron star (albeit at a smaller rate of 0.1 Gpc −3 yr −1 ), the formation of Thorne-Zytkow objects (Thorne & Zytkow 1975) when a neutron star in the disk is unable to tidally disrupt a stellar companion due to a large stellar radius, the tidal disruption of white dwarfs by stellar-mass BHs, with unique signatures (Maguire et al 2020), and the accretion induced collapse of neutron stars (Perna et al 2021b) and white dwarfs (Zhu et al 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…The unique environments in AGN disks are expected to give rise to a wealth of other interesting phenomena, such as the tidal disruption of a star by a neutron star (albeit at a smaller rate of 0.1 Gpc −3 yr −1 ), the formation of Thorne-Zytkow objects (Thorne & Zytkow 1975) when a neutron star in the disk is unable to tidally disrupt a stellar companion due to a large stellar radius, the tidal disruption of white dwarfs by stellar-mass BHs, with unique signatures (Maguire et al 2020), and the accretion induced collapse of neutron stars (Perna et al 2021b) and white dwarfs (Zhu et al 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…The highly relativistic electromagnetic signatures of 𝛾-ray bursts (GRBs) and the accretion induced collapse of neutron stars (NS) into BHs have been recently explored (Zhu et al 2020(Zhu et al , 2021aPerna et al 2021b,a). Recently, Zhu et al (2021b) suggested that type Ia supernovae may potentially be observable in AGN discs. However, a detailed model for the interaction of a non-relativistic SN explosion with the AGN disc and its observational signatures is still lacking.…”
Section: Introductionmentioning
confidence: 99%